COVID-19, Impact of External Environment in the Formation of Students’ Satisfaction as well as Subjective Well-Being in the Context of E-learning - Shah, Hassan Jalil; Muhammad Danish Habib; Dr. Abdul Qayyum (Pakistan Business Review, 2021)
The complete lockdown imposed worldwide in the wake of COVID-19 has equally affected the education sector. Whereas the entire paradigm of education switched over to the e-Learning mode of education, the transit has not been free of friction. Students have generally expressed their frustration over the mode of delivery of education with frequent complaints of lack of connectivity and inability of creation of optimum learning environment. This paper intends to explore the role of external influences (i.e. E-environment and Technology-Internet-Quality) correlated with satisfaction of the customer, leading to customers’ subjective well-being. The study, explores the fundamental role of the environmental and technological perspectives in the generation of consumer’s response behaviors through the cognitive process in the context of e-learning. Using a purposive sampling technique, data was accumulated from three universities having e-learning as their mode of delivery of education. 1,338 students (customers) of e-learning responded to the survey questionnaire floated through google doc. The results corroborate the assertion laid in the hypothesis that e-environment, psychological and technological influences of the students (customers) play a significant role in the development of customer satisfaction which leads to the subjective well-being. The findings of the study contribute in building a rigor of social cognitive theory in the context of e-learning. Consumer’s cognitive process postulate that customer’s e-environment, as well as and technological factors significantly impact the psychological characteristics which ultimately affects response behaviors of customers. Aimed at improving the learning skills and enhancing the learning motives, this study would contribute in making good relationships towards that end.Thus far, determining the concurrent impact of customer satisfaction and subjective well-being in the divergent fields of technology, consumer behaviour and individual psychology have remain unexplored. This foray would therefore help in understanding the complex relationship, specially when viewed in the backdrop of students’ dissatisfaction with the e-learning mode of education in the obtaining environment of COVID-19. Besides filling the existing void in the literature, this study will thus help the policy makers, academicians and practitioners to address these intricate issues affecting students satisfaction so as to smoothly role out the e-learning mode of education. Thus, the current study also intends to fill these gaps and contributes to the existing literature on these issues besides improving the understanding of the academicians, practitioners and policy makers regarding these major issues working behind e-learning implementation.Keywords: COVID-19, E-learning, E-environment, Technology-Internet-Quality, Subjective well-being.
Keywords: COVID-19, E-learning, E-environment, Technology-Internet-Quality, Subjective well-being.